Coaptation and functional bracing of adolescent humeral shaft spiral fracture: a case report and review of literature - Thiagarajan Singaram, Thiyagarajan; Harshavardhan J.K., Giriraj (International Journal of Research in Orthopaedics, 2020)
Adolescent humerus shaft fractures are uncommon. Direct injuries lead to transverse fractures and indirect injuries lead to spiral and most oblique fractures. There is fracture displacement, angulation and internal rotation of the proximal fragment. There is difficulty in maintaining reduction after closed manipulation of spiral fractures. Paediatric humeral shaft fractures are treated by elastic intramedullary nails more often nowadays. We present a case of isolated spiral fracture of the middle1/3rd and distal 1/3rd junction of the humerus shaft with displacement and angulation treated successfully with closed reduction, coaptation U slab followed by functional orthosis.